About public health policies in the new century (2000)
Several subjects of public health policies are analyzed from different points of view, bearing in mind the line of coherence of their universal, global and integral character. Themes such as "Health for All", understood as a universal policy at the close of this century, are included. Around it other recent approaches are considered which are also related between them: the subject of health promotion in its broad vision from the guidelines of the Ottawa (Canada) letter, and the public health policies in a version inscribed within the most recent strategies in the health field. Health is understood from a perspective of social product related to the living conditions of peoples, to their possibilities of having access to welfare, and to their free determination and autonomy in their decisions. In this sense, several methodologies about policy formulation are approached, emphasizing the political referent of collective order and the participation of the different actors as crucial aspects for effective decision making.